Farmers' Response To The Rice Farming Business Insurance Program (AUTP) In Kramatwatu District - Setiawan, Mohamad Arief; Kalfin, Kalfin (iora, 2021)
The agricultural sector is one attempt most vulnerable to the negative effects of climate change. Behavior extreme climate led not deficient or damage to the irrigation network, the farming, and agricultural infrastructure. To minimize risk losses from a threat that happened on agriculture. One alternative instrument risk management worth considering is the presence of agricultural insurance. The purpose of this research is to study a sort of descriptive program, identify, analyze, and describe a characteristic response of farmers on the insurance program rice farming (AUTP) in the Kramatwatu district. The methodology used in research is the method survey; the location of research is purposive on the basis that Kramatwatu district is a district that members of the farmer's group have an interest in the participation of the highest AUTP program. An analysis of the data used was analysis descriptive is used to give the percentage identification elements communication and the effectiveness of communication. While relations communication element to analyze the effectiveness of communication producers and farmers in the activities of the barns using analysis inferential through correlation test rank spearman. Based on the results of the study it can be seen that the cognitive response category agreed (46%), effective response category agreed (26%), conative response categories agreed (23%), and The results of this study indicate that of all factors associated with the level of farmer participation the AUTP program in Kramatwatu sub-district has an average valuation that includes the income and education factors have a weak but relative relationship, then the age factor and the area of land do not give any relation to the farmer's participation in the AUTP program.